Intraspecific trait variation and the leaf economics spectrum across resource gradients and levels of organization. Issue 5 (30th March 2018) - Fajardo, Alex; Siefert, Andrew
Abstract: Understanding patterns of functional trait variation across environmental gradients offers an opportunity to increase inference in the mechanistic causes of plant community assembly. The leaf economics spectrum (LES) predicts global tradeoffs in leaf traits and trait‐environment relationships, but few studies have examined whether these predictions hold across different levels of organization, particularly within species. Here, we asked (1) whether the main assumptions of the LES (expected trait relationships and shifts in trait values across resource gradients) hold at the intraspecific level, and (2) how within‐species trait correlations scale up to interspecific or among‐community levels. We worked with leaf traits of saplings of woody species growing across light and soil N and P availability gradients in temperate rainforests of southern Chile. We found that ITV accounted for a large proportion of community‐level variation in leaf traits (e.g., LMA and leaf P) and played an important role in driving community‐level shifts in leaf traits across environmental gradients. Additionally, intraspecific leaf trait relationships were generally consistent with interspecific and community‐level trait relationships and with LES predictions—e.g., a strong negative intraspecific LMA–leaf N correlation—although, most trait relationships varied significantly among species, suggesting idiosyncrasies in the LES at the intraspecific level.